Clinical characteristics of fatal cases of hand, foot and mouth disease in children - Zhang, Xue; Sun, Ruiyang; Hou, Jiapu; Jia, Wanyu; Li, Peng; Shi, Shengli; Song, Chunlan; Cheng, Yibing (Frontiers in Pediatrics, 2025)
BackgroundHand, foot and mouth disease (HFMD) is a common infectious disease that continues to pose a serious threat to children. The purpose of this study was to analyze the clinical characteristics and causes of death of mortality among children with fatal HFMD.MethodsClinical data from children who had HFMD and died in the pediatric intensive care units of Henan Children's Hospital from January 2014 to December 2019 were retrospectively analyzed.ResultsThirty-one fatal cases were identified (19 males, 12 females), aged 9–47 months, all without underlying disease. Mortality was highest among children aged 12–36 months. A declining trend in deaths was observed from 2014 to 2019. The median duration of disease was 4.5 days. Common clinical manifestations included fever, rash, dyspnea, disturbance of consciousness, abnormal heart rate and limb tremors. Neurogenic pulmonary edema (NPE) was the primary cause of death in 24 cases, followed by brainstem encephalitis in 6 cases and cerebral hernia in 1 case. Enterovirus A71 (EV-A71) was the predominant pathogen (27 cases, 87.10%).ConclusionAlthough the HFMD mortality has shown a downward trend in recent years, children younger than 36 months infected with EV-A71 remain at high risk of fatal outcomes. NPE and brainstem encephalitis are the leading causes of death in children with HFMD.